Assessment of Heavy Metals in Women’s Dyed Hair Samples in the South of Libya - Salha Ali Fatah; Ayiman Ahmed Mustafa; Wafa Khalleefah Amhimmid (African Journal of Advanced Pure and Applied Sciences, 2023)
Heavy metals apparent toxicity to humans is a result of long term or extreme level exposure to pollutants like cosmetics and hair dyes. In this study, the concentrations of some toxic metals have been measured in different hair samples dyed by products sold at local markets in Taraghun, Libya. Five different brands used by eight ladies. Hair samples were prepared by acid digesting using Microwave oven. The heavy metals (As, Ba, Cd, Cr, Cu, Pb, and Zn) concentrations in hair samples were evaluated by inductively coupled plasma mass spectrometry ICP- MS. The sample’s concentration of heavy metals ranged from (1.18- 4.18 ppm) for Arsenic, (15.22- 3729ppm) for barium, (0.002 -1.91 ppm) for cadmium, (2.08- 5.80ppm) for chromium, (13.0-34.9ppm) for copper, (4.19-52.8ppm) for lead, and (109.6-258.6 ppm) for zinc. High levels of toxic metals could put-up potential health hazard to consumers such as skin problems or cancer.